Effect of Exercise on Mortality and Recurrence in Patients With Cancer: A Systematic Review and Meta-Analysis. (May 2020) - Morishita, Shinichiro; Hamaue, Yohei; Fukushima, Takuya; Tanaka, Takashi; Fu, Jack B.; Nakano, Jiro
Purpose: Exercise could lower the risk of cancer recurrence and improve mortality, exercise capacity, physical and cardiovascular function, strength, and quality of life in patients with cancer. This systematic review and meta-analysis of randomized controlled trials (RCTs) aimed to determine the effects of exercise on mortality and recurrence in patients with cancer.Methods: We searched for articles published before May 2019 in MEDLINE, CINAHL, the Cochrane Library, Scopus, ProQuest, and PEDro. We included RCTs of exercise interventions, such as resistance exercise and aerobic exercise, in patients with cancer that evaluated the risk of mortality and recurrence. The standardized mean difference with 95% confidence intervals (CIs) was calculated for quantitative indices. The random-effect model was used as the pooling method.Results: Of 2868 retrieved articles, 8 RCTs were included in the meta-analysis, with a mean PEDro score of 4.50 (SD = 1.25). Exercise significantly reduced the risk of mortality in patients with cancer and in cancer survivors (risk ratio [RR] = 0.76, 95% CI = 0.40-0.93, I 2 = 0%, P = .009). Exercise significantly reduced the risk of recurrence in cancer survivors (RR = 0.52, 95% CI = 0.29-0.92, I 2 = 25%, P = .030).Conclusion: This study found that exercise has a favorable effect on mortality and recurrence in patients with cancer. However, the effect could not be fully determined due to data insufficiency.